KAJIAN SIFAT KIMIA TANAH SAWAH PADA BEBERAPA LOKASI DI DISTRIK SEMANGGA - Wa Ode Asryanti Wida Malesi; Mega Ayu Yusuf; Parjono; Maya Sari Rupang (JURNAL AGRIMENT, 2023)
The aim of the research was to determine the chemical properties of the soil in the rice fields of the Semangga district. The research method used is survey method. This research was conducted in 3 villages in the Semangga district which had rice fields. Soil sampling was carried out in a composite manner by taking soil samples at a depth of 0-25 cm. Soil samples were analyzed at the Bogor Environmental Biotechnology Laboratory. Based on the analysis results obtained data on soil chemical properties pH, C-organic, and cation exchange capacity (CEC). Based on the research results, the pH value was obtained from neutral to acid. The neutral pH value was found at location A, which was 7.61, at location B, the pH value was 4.42, and at location C, the pH value was 4.75. C-organic from the results of research at 3 locations is classified as moderate to high. At location A the soil organic matter value was 1.19, at location B the soil organic C value was 6.30 and at C location the soil organic C value was 4.11. Cation exchange capacity (CEC) at the study site was classified as moderate to high. At location A it has a cation exchange capacity value of 21.46 cmol/kg, at location B it has a cation exchange capacity value of 30.00, and at location C it has a cation exchange capacity value of 29.12.